Determinant factors of income inequality: evidence from a Portuguese region - Crespo, N.; Simões, N.; Diogo, A. P. (Economics Bulletin, 2012)
We propose a new methodology, based on bilateral comparisons between households, to analyze the determinants of income inequality, and confirm the influence of variables related to: (i) socio-economic characteristics of the household, (ii) dimension and composition of the household, (iii) the number of households in the residence, and (iv) socio-economic characteristics of the individual of reference.